[Rezension von: Feldmeier, Reinhard, 1952-, God becoming human : Incarnation in the Christian bible] - Grillo, Jennie (The journal of theological studies, 2025)
This book completes what the authors call the ‘diptych’ of the collaborative work begun in their earlier Der Gott der Lebendigen. Eine biblische Gotteslehr